1974
DOI: 10.1111/j.1651-2227.1974.tb04842.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Study of the Renal Response to an Oral Salt Load in Preterm Infants

Abstract: ABSTRACT. Aperia, A., Broherger, O., Thodenius, K. and Zetterström, R. (Department of Paediatrics, Karolinska Institutet, S:t Göran's Children's Hospital, Stockholm, Sweden). Developmental study of the renal response to an oral salt load in preterm infants. Acta Paediatr Scand 63: 517, 1974.—An evaluation of sodium homeostasis in 44 preterm infants with gestational ages between 29 and 37 weeks has been carried out during the first week after birth and until time of expected term. The natriuretic response to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
17
0
2

Year Published

1978
1978
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 32 publications
6
17
0
2
Order By: Relevance
“…The relative immaturity of renal function in very low birth wt and premature neonates seems to be important in the pathogenesis of hyponatremia. Premature neonates exhibit a greater natriuresis and a lower GFR in response to oral salt loading when compared to full-term neonates (5,6). This is consistent with histopathologic studies that show that glomerular formation in the human infant is not complete until late in gestation (7), whereas tubular development is not complete until 1 y after birth (8).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The relative immaturity of renal function in very low birth wt and premature neonates seems to be important in the pathogenesis of hyponatremia. Premature neonates exhibit a greater natriuresis and a lower GFR in response to oral salt loading when compared to full-term neonates (5,6). This is consistent with histopathologic studies that show that glomerular formation in the human infant is not complete until late in gestation (7), whereas tubular development is not complete until 1 y after birth (8).…”
supporting
confidence: 76%
“…As the kidney matures it becomes capable of increasing distal tubular sodium reabsorption to compensate for any increased distal tubular fluid delivery. (Pediatr Res 26: [6][7][8][9][10]1989) Abbreviations FRN,, fractional reabsorption of sodium FR,,i, fractional reabsorption of lithium uN,,v, uKV, UclV, Uc.V, renal excretion rate of sodium/ potassium/chloride/calcium may be responsible for neonatal hyponatremia. However, subsequent investigations have shown that a characteristic of this defect is decreased proximal tubule reabsorption of sodium (2) implying that renal insensitivity to aldosterone may be only partially responsible.…”
mentioning
confidence: 99%
“…Subsequently, these findings have been confirmed and several fac tors have been considered which might be involved in renal salt wasting, however, its pathomechanism has not been clearly establish ed (1,12).…”
mentioning
confidence: 82%
“…In an attempt to delineate the specific tubular defect in sodium reabsorption in low-birth-weight neonates, fractional sodium excretion (C Na/Ccr)> distal tubular sodium delivery (C Na+CHjo), and distal tubular sodium reabsorption |(CH:o/C H ,o+CNa) x 100] were determined in 8 healthy premature and 10 full-term newborn infants. The mean birth weight was 1,701 g (range: 1,240-2,120 g) and the mean gestational age was 32.6 weeks (range: 28-35 weeks) for premature; and 3,199 g (range: 2,670-3,670 g) and 38.9 weeks (range: 38-41 weeks) for full-term neonates.It was demonstrated that the significantly higher fractional sodium excretion in premature infants (1.44 ± 0.33 SE versus 0.36 ± 0.09%, p < 0.01) resulted from significantly decreased proximal (CNa+CH2o : 0.674 ± 0.105 versus 0.360 ± 0.069 ml/min/1.73 m2, p < 0 .0 5 ) and distal [(CH2o/CH2o +CNa) x 100:69.9 ± 3.3 versus 85.8 ± 3.4%, p < 0.01) tubular sodium reabsorption.In 1970 while investigating the renal control of neonatal acid-base homeostasis, we demon strated for the first time the increased urinary sodium loss in low-birth weight premature in fants (10).It has also been shown that the renal sodium conservation improved significantly with in creasing gestational (1,5,17,22) and postnatal (1,8,10,15,21) age. Subsequently, these findings have been confirmed and several fac tors have been considered which might be involved in renal salt wasting, however, its pathomechanism has not been clearly establish ed (1, 12).…”
mentioning
confidence: 99%
“…Urine osmolality was measured cryoscopically using a Knauer osmometer [11], creatinine concentration according to the modified Jaffé's method [12]. Urinary AQP2 levels were determined by using highly sensitive radioimmunoassay as described by Wen et al [5].…”
Section: Methodsmentioning
confidence: 99%